Religious-Based Peer Education in Preeclampsia Prevention: Social Cognitive Theory and Information, Motivation, Behavioral Skill Model Approach to Improve Preeclampsia Preventive Behavior in Indonesia - Rahmawati; Murti, Bhisma; Widyaningsih, Vitri (Public Health of Indonesia, 2024)
Background:Preeclampsia is the second leading cause of maternal death, largely due to the failure to identify the condition early. Prevention behaviors for preeclampsia in pregnant women can be developed through the Social Cognitive Theory (SCT) and the Information-Motivation-Behavioral Skills (IMB) Model. Utilizing religious organizations with unique values and cultures to foster high levels of compliance, a Religious-Based Peer Education approach can optimize these preventive efforts. Objective:This research aims to analyze the influence of knowledge, skills, motivation, observational learning, husband's support, and self-efficacy on the formation of preeclampsia prevention behaviors. Methods:A non-equivalent pre- and post-test design was conducted in Bojonegoro district from August 2022 to February 2023. The sample consisted of 179 pregnant women in the intervention group and 168 in the control group. The intervention involved Religious-Based Peer Education, with peers being members of the Muslimat NU religious organization, while the control group received routine assistance from existing health cadres. Data were analyzed using path analysis. Results:The mean scores for knowledge, skills, and behavior in the intervention group were significantly higher than those in the control group (13.81 vs. 12.34; 2.37 vs. 1.95; 30.33 vs. 28.19; p < 0.001). The strongest factors influencing the formation of preeclampsia prevention behavior were screening skills (b = 0.74, p = 0.010; 95% CI: 0.03–0.23) and self-efficacy (b = 0.36, p = 0.010; 95% CI: 0.23–0.48). Conclusion:The SCT and IMB models, when applied through Religious-Based Peer Education, have proven effective in improving preeclampsia prevention behaviors. Ongoing training for peers and consistent support for pregnant women are essential to identify high-risk pregnancies and prevent maternal complications. Keywords: social cognitive theory; information-motivation-behavioral skills model; preeclampsia; religious-based peer education; behavior